(untitled) (ModaPalavra e-periódico, 2018)
Contemporaneity is considered as the era of brands, in which it is omnipresent and omnipotent. The objective of this research was to study the social place of the brand in contemporaneity, configured in the social and cultural spheres, in order to identify the occurrence of the process of valorization of its image. The symbolic capital raises the economic capital and creates an identity relationship with its customers. The massive investment in communication in the various ways causes inculcation of the brand in the minds and includes it in the habitus of the society. It presents the case study of the brand management of Havaianas, that managed to transform in two decades its symbolic value from popular to worshiped by all social classes. As a result, the brand generates identity, stability, satisfies desires and unites social groups.